Study of semi deterministic model for fifth-generation (5G) wireless networks - Supachai Phaiboon (2020)
© 2019, Springer Nature Singapore Pte Ltd. This paper presents study of path loss models of fifth generation (5G) wireless communication systems. Propagation parameters such as path loss at reference distance (PL(d0)), path loss exponent (PLE) and standard deviation of the zero-mean Gaussian random both line-of-sight (LOS) and non line-of-sight (NLOS) are compared at the frequencies of 28, 38 and 73 GHz. Omni directional propagation large-scale path loss measured data from two downtown Cities are used. This paper also compares with semi deterministic models such as WI model and Xia model for present 4G network in order to develop the semi deterministic model for 5G networks.